2016
DOI: 10.21859/isv.10.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk factors of Akabane Virus Infection in cattle from Khouzestan Province of Iran

Abstract: Background and Aims: Akabane virus is an arbovirus in the genus Orthobunyavirus of the family Bunyaviridae that can affect ruminants such as cattle, sheep and goats. This arthropodborne virus is transmitted by either mosquitoes or midges and has been identified as a cause of outbreaks of reproductive disorders (abortions, premature births, and stillbirths) and congenital malformations (arthrogryposis, hydranencephaly and microencephaly) in cattle, sheep and goats. The aim of the present study was to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…It was also found that the seroprevalence of the AKAV infection is significantly related to lactation conditions (lactating or heifer) (21). In another study, age, race, and geographical location showed a significant positive relationship with the prevalence of infection, while history of abortion did not show a relationship with the prevalence of infection (22). Furthermore, gender showed a strong relationship with the prevalence of infection, which is in accordance with the present results (5).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It was also found that the seroprevalence of the AKAV infection is significantly related to lactation conditions (lactating or heifer) (21). In another study, age, race, and geographical location showed a significant positive relationship with the prevalence of infection, while history of abortion did not show a relationship with the prevalence of infection (22). Furthermore, gender showed a strong relationship with the prevalence of infection, which is in accordance with the present results (5).…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that the prevalence of AKAV infection can differ across various regions of the same province. In a similar study conducted in Khuzestan, the prevalence of infection in different cities of the province differed from each other (22). These results are in agreement with other studies on the AKAV (2,18).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations